A di-electrophoretic simulation procedure of iron-oxide micro-particle drug attachment system for leukemia treatment using COMSOL software: a potential treatment reference for LMICs - Kiwumulo, Henry Fenekansi; Muwonge, Haruna; Ibingira, Charles; Lubwama, Michael; Kirabira, John Baptist; Ssekitoleko, Robert Tamale (Frontiers in Medical Technology, 2023)
Background: Leukemia encompasses various subtypes, each with unique characteristics and treatment approaches. The challenge lies in developing targeted therapies that can effectively address the specific genetic mutations or abnormalities associated with each subtype. Some leukemia cases may become resistant to existing treatments over time making them less susceptible to chemotherapy or other standard therapies.Objective: Developing new treatment strategies to overcome resistance is an ongoing challenge particularly in Low and Middle Income Contries (LMICs). Computational studies using COMSOL software could provide an economical, fast and resourceful approach to the treatment of complicated cancers like leukemia. Using COMSOL Methods: Multiphysics software, a continuous flow microfluidic device capable of delivering antileukemia drugs to early-stage leukemia cells has been computationally modeled using dielectrophoresis (DEP).Results: The cell size difference enabled the micro-particle drug attachment to the leukemia cells using hydrodynamic focusing from the dielectrophoretic force. This point of care application produced a low voltage from numerically calculated electrical field and flow speed simulations. Conclusion: Therefore, such a dielectrophoretic low voltage application model can be used as a computational treatment reference for early-stage leukemia cells with an approximate size of 5 micrometers.